2018
DOI: 10.1175/wcas-d-17-0105.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Political Ideology and Socioeconomic Vulnerability on Perceived Health Risks of Heat Waves in the Context of Climate Change

Abstract: Vulnerability and resilience to extreme weather hazards are a function of diverse physical, social, and psychological factors. Previous research has focused on individual factors that influence public perceptions of hazards, such as politics, ideology, and cultural worldviews, as well as on socioeconomic and demographic factors that affect geographically based vulnerability, environmental justice, and community resilience. Few studies have investigated individual socioeconomic and racial/ethnic differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…Note that the measured temperature data are not part of the current paper. [26] Has been substituted in the study by 'not living alone' Suffering health impacts during heat [27] Included Political orientation [28] Political orientation in the USA not applicable for Germany Climate change beliefs [28] Substituted by item 'heat seen as a problem' Ethnic minority [29] Not applicable in sample Time working outside [29] Excluded, study focusses on temperatures at home Subjective health status [30] Not necessary because health implications during heat are asked; substituted by subjective heat sensitivity…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the measured temperature data are not part of the current paper. [26] Has been substituted in the study by 'not living alone' Suffering health impacts during heat [27] Included Political orientation [28] Political orientation in the USA not applicable for Germany Climate change beliefs [28] Substituted by item 'heat seen as a problem' Ethnic minority [29] Not applicable in sample Time working outside [29] Excluded, study focusses on temperatures at home Subjective health status [30] Not necessary because health implications during heat are asked; substituted by subjective heat sensitivity…”
Section: Methodsmentioning
confidence: 99%
“…For example, in Phoenix, Arizona, the perception of heat risk is higher among Hispanics; among women and young people [24]; among vulnerable groups, people with one or more chronic diseases or of low income [25]; among those married [26]; and among those suffering from more health impacts during heat [27]. Furthermore, it is known that the perception of heat risks can also depend on political orientation and climate change beliefs [28]; being part of an ethnic minority; the amount of time working outside [29]; and people's subjective health status [30]. The results show that the factors associated with heat risk perception are divergent and depend on the region, its climate conditions and the demographic factors of the people participating.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Leiserowitz (2006) found that liberals tend to perceive greater risks associated with climate change compared to conservatives. Similarly, Cutler et al (2018) found that political ideology is one of the most powerful predictors of perceived health risks associated with extreme heat.…”
Section: Influence Of Political Ideology and Health Status On Harm Perception And Policy Supportmentioning
confidence: 94%
“…Relative to conservatives, liberals are more likely to believe climate change is happening and human-caused, to be worried about it, and to express greater support for action to address it (Ballew et al, 2019; Hamilton, 2008; McCright, 2010; Wood & Vedlitz, 2007). Political ideology is also a significant predictor of perceived harm caused by climate change (Bolsen et al, 2018; Cutler et al, 2018; Leiserowitz, 2006; McCright, 2011). For example, Leiserowitz (2006) found that liberals tend to perceive greater risks associated with climate change compared to conservatives.…”
Section: Influence Of Political Ideology and Health Status On Harm Perception And Policy Supportmentioning
confidence: 99%
“…It is inferred that in northern Shaanxi region, due to the relatively harsh environment, conservative ideological concepts, serious soil erosion, and frequent disasters, education degree has a smaller impact on climate change risk response perception [35]. Instead, concern degree for climate change issues and climate change reason perception influence the causal path of climate change risk perception [36]. In southern Shaanxi, the mountains and rivers are beautiful, so it is less hit by natural disasters.…”
Section: Comparative Analysismentioning
confidence: 99%